Relationship between bean leaf structure and the Glomerella cingulata f.sp. phaseoli preinfection - Jerba, Vanessa de Fátima; Rodella, Roberto Antonio; Furtado, Edson Luiz (Pesquisa Agropecuaria Brasileira, 2005)
The objectives of this work were to measure the secondary vein area and to quantify the trichomes of leaf surface in bean cultivar susceptible (Carioca), medium resistant (Pérola) and resistant (IAPAR-81) to anthracnose, and to observe relationships between leaf blade characteristics with the preinfectional stages. In order to measure the secondary vein area, sample leaf pieces were fixed in FAA 50 and conserved in 70% alcohol. These leaf samples were infiltrated in glycol metacrylate resin, cut transversally and stained with toluidine blue. The trichomes were quantified in epidermical impressions in projection microscopy. The material for preinfection analysis was fixed in 2.5% glutaraldehyde and processed to study the scanning electron microscopy. The resistant cultivar showed minor secondary vein area and high pilosity than the cultivar medium resistant and susceptible. In the resistant cultivar, due to minor vein area and high pilosity, the pathogen stayed on the vein and involved on the trichomes. In susceptible cultivar, with high vein and minor pilosity, necrosis and fungal structure on the leaf surface were observed. The results show a relation between the minor vein and high leaf trichomes quantity with the resistance to the anthracnose in pathogen preinfection stages.